2021
DOI: 10.18203/2320-6012.ijrms20214436
|View full text |Cite
|
Sign up to set email alerts
|

Common sources of radiations in a medical environment

Abstract: Use of radiation is now a days so common in most of the tertiary care hospitals for diagnostic and therapeutic purpose. The ionizing radiation provides many benefits in both diagnostic as well as therapeutic interventions, but they are also potential harmful. Radiation risks, exposure and mitigation strategies should always be in mind while using to an individual (public, radiation worker, and patient) and the environment should not exceed the prescribed safe limits. Regular monitoring of hospital area and rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…A survey found that the most significant amounts of released radionuclides in the Fukushima accident were cesium, strontium, iodine and cobalt [70]. These radionuclides are also often found in waste generated from industrial and medical radioisotope applications [40]. That is why further studies that we mentioned in this paper focus on these radionuclides.…”
Section: Skin Burns •mentioning
confidence: 92%
“…A survey found that the most significant amounts of released radionuclides in the Fukushima accident were cesium, strontium, iodine and cobalt [70]. These radionuclides are also often found in waste generated from industrial and medical radioisotope applications [40]. That is why further studies that we mentioned in this paper focus on these radionuclides.…”
Section: Skin Burns •mentioning
confidence: 92%